Perwujudan Demokrasi Ekonomi Melalui Hyperlocal Tokopedia - Ningsih, Sabda (Jurnal Ilmiah Hubungan Internasional, 2023)
The Covid-19 pandemic has become a concern for all governments globally because it can affect the economy. In Indonesia, one of the government's focuses is how to solve problems related to MSMEs facing the threat of bankruptcy and the government's choice is to cooperate with e-commerce through hyperlocal. Hyperlocal for some researchers has the effect of changing the structure of cooperation and the logic of business organizations. However, the author himself argues that hyperlocal issues also have a role in identity transformation. This is based on the findings of several previous studies, that hyperlocal communication media influences the distribution of culture and the identity of certain community groups. By using the analytical framework of post-Fordism and constructivism, the author finds that Hyperlocal Tokopedia have influenced the identity of MSMEs in understanding "who am I?" and "what will I do?". In addition, the interaction between Tokopedia and MSMEs, which initially had different identities, showed the last optimistic result. This shows that the interaction between identities in constructivism can be intentional by external actors. While related to post-Fordism, the results of this study only strengthen that the transformation of economic society is not economic, political, and cultural. But there is also a transformation of understanding of themselves. Keywords: Hyperlocal; Constructivism; Post-Fordism; Knowledge-Economy; Economic Globalization